Clinico-pathological spectrum of vesiculobullous diseases: A prospective cross-sectional study. - Naik, Dr. Nidhi; Srinath, Dr. Sudhamani; Dive, Dr. Prakash (Student's Journal of Health Research Africa, 2025)
Background: Vesiculobullous lesions are a heterogeneous group of disorders characterized by fluid-filled cutaneous lesions of varied etiology, including autoimmune, genetic, drug-induced, and infectious causes. Due to overlapping clinical presentations, diagnosis based on clinical features alone is challenging. Histopathology and direct immunofluorescence (DIF) are crucial adjuncts, enhancing accuracy, guiding therapy, and informing prognosis. Objectives: To evaluate the histopathological features of vesiculobullous skin disorders, correlate them with clinical findings, and assess the utility of DIF in achieving a definitive diagnosis. Additional objectives were to classify lesions by age, sex, and distribution. Methods: This prospective cross-sectional study was conducted in the Department of Pathology, D.Y. Patil School of Medicine, Navi Mumbai. A minimum of 50 clinically suspected cases were enrolled; 56 were analyzed. Clinical history, dermatological examination, and punch biopsies were performed. Routine histopathology was supplemented with DIF in selected cases. Data were analyzed using descriptive statistics. Results: The most commonly affected age group was 21–30 years (23.2%). A slight male predominance was noted (53.6%), with a male-to-female ratio of 1:0.87. The trunk was the most frequent site (41%). Clinically, pemphigus vulgaris was most common (23.2%), followed by bullous pemphigoid (12.5%) and Stevens–Johnson syndrome (12.5%). Histopathology revealed intraepidermal blisters as the most frequent pattern (35.7%). DIF showed granular IgG and C3 positivity in pemphigus vulgaris and linear IgG/C3 deposition along the dermoepidermal junction in bullous pemphigoid. Conclusion: Clinical features alone are insufficient for accurate categorization of vesiculobullous lesions. Histopathology remains the gold standard, while DIF provides valuable confirmation when findings are inconclusive. Integrating these approaches ensures precise diagnosis, timely treatment, and better prognostic guidance, particularly in autoimmune bullous diseases. Recommendations: Routine biopsies with clinicopathological correlation should be emphasized. DIF should be integrated whenever feasible, with improved accessibility and clinician–pathologist collaboration to optimize patient outcomes.